A CROSS-SECTIONAL OBSERVATIONAL STUDY ON RURAL INSIGHTS: MATERNAL BODY METRICS, PRE-PREGNANCY BODY MASS INDEX, AND FETAL DEVELOPMENT. - Kiran, Chandra; Madhu, Nimisha (Student's Journal of Health Research Africa, 2024)
Background: Understanding the association between maternal health and fetal development is crucial, especially in rural settings where healthcare and nutritional resources are often limited. This study explores the impact of maternal anthropometric measurements and pre-pregnancy Body Mass Index (BMI) on fetal growth parameters, focusing on a rural population to highlight unique challenges and patterns that might differ from urban experiences. Methodology: A cross-sectional study was conducted with 240 pregnant women in their first trimester. Comprehensive sociodemographic and anthropometric data were collected, and the study focused on maternal pre-pregnancy weight, height, and BMI as primary variables. Data analysis was performed using SPSS 17.0. Results: The study found no instances of macrosomia but noted a significant number of low birth weight (LBW) babies. Significant differences were observed in the mean pre-pregnancy weight and BMI (18.95 ± 1.75 kg/m² vs. 19.85 ± 2.80 kg/m², p=0.003) between the LBW and normal birth weight groups, indicating that lower maternal weight and BMI before pregnancy are related with a greater risk of LBW. Established correlations between maternal pre-pregnancy weight/BMI and neonatal metrics, along with sociodemographic data, highlighted the significant impact of low education and income levels on LBW risk, emphasizing socioeconomic factors' importance in maternal and fetal health. Conclusion: The study confirms the significant impact of maternal anthropometric measurements on neonatal outcomes, particularly in a rural context. It emphasizes the need for comprehensive maternal healthcare services focusing on nutrition and education to improve fetal growth outcomes. Recommendations: Policies and healthcare strategies should be tailored to meet the needs of rural populations, ensuring better maternal and child health. Future research should incorporate detailed dietary and health behavior data to elucidate the pathways linking maternal health to fetal outcomes and explore the impact of interventions targeting maternal nutrition and healthcare access.